High Efficiency Harmonic Harvester Rectenna for Energy Storage Application - Deepak Kumar; Kalpana Chaudhary (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This work presents harmonic harvester Rectenna integrated power management circuitry for improving RF-DC power conversion efficiency. The circuitry is developed for battery charging or energy storage application; resistance emulation method is used to realize a matching load resistance at output terminals. The proposed technique is useful for harvesting near maximum output power from the dual rectifiers (fundamental and harmonics) independently. Also, it delivers the combined maximal power to the energy storage cell. The power management module based on dual input buck-boost converter with simple open loop control is utilized.